Nutritional Composition and Microbial Quality of Processed Edible Dung Beetle Larvae (Scarabaeus satyrus) - Fedha, Monica S.; Otiato, D.A.; Kinyuru, J.N. (East African Journal of Science, Technology and Innovation, 2024)
The larva of the African dung beetle (Scarabaeus satyrus) is a delicacy in human diets. This insect is presumed to be nutritious, while its safety aspects are in doubt. The objective of this study was to evaluate the nutritional composition and microbial quality of the processed larvae using standard methods of analysis. The larvae were collected from farms in three regions of Bungoma, Kakamega and Siaya using random sampling. The samples were subjected to toasting, oven drying and roasting. A factorial arrangement was used in the study and data analysed using generalized linear models. The study focused on proximate composition of Moisture, protein, fat, fibre, and ash, elemental Mineral analysis as well as microbial content of total viable counts (TVC), Salmonella, Staphylococcus sp., Coliforms and yeasts and moulds. Results showed that S. satyrus larvae contained crude protein of 59.65 - 66.05 g/100g, crude fat (15.18-16.87 g/100g) and crude ash (4.45-4.67g/100g) on dry weight basis. The mineral Iron was the most abundant trace element with a value of 19.19mg/100g, while phosphorus was the most plentiful macro mineral with 331.42mg/100g. Salmonella sp. was not detected in any of the samples. Total viable counts, Staphylococcus aureus, Escherichia coli, yeasts and moulds were present with raw samples from Bungoma County containing highest amounts of total viable counts (6.20±0.06 Log cfu/g). The roasting technique had the greatest effect of reduction of viable counts by over two log cycles to 4.15±0.05 Log cfu/g. The study showed that heat processing is effective in lowering the microbial load to levels that are safe for human consumption. These findings indicate that S. satyrus is a rich source of macro nutrients and minerals, and is recommended as an alternative protein source.
Keywords: Nutritional Composition; Microbial Quality; Mineral; Scarabaeus satyrus